An operator inequality - P. D. Siafarikas (International Journal of Mathematics and Mathematical Sciences)
An inequality is proved in abstract separable Hilbert space H where A and B are bounded self-adjoint positive operators defined in H such that R(A)=R(B) and R(A) is closed.